Development and validation of afterlife beliefs and expectations inventories for Jordanian and Malaysian Muslim youth in selected universities - Al-Issa, Riyad Salim Issa (2022)
Despite the centrality of afterlife reward and punishment beliefs and expectations (ARPB&E) in the life of Muslim youth, there is a dearth of valid instruments to measure ARPB&E. As a result, few empirical studies have sought to understand how ARPB&E affects the social behavior of young Muslims. The aim of the study was to develop scales to measure ARPB&E and to examine its relationship with prosociality-related variables (integrity, rule-breaking ability and self-control) and death attitudes among Muslim youth. The study had four objectives. The first objective was to develop an instrument to measure Afterlife Reward and Punishment (ARPB) beliefs among Muslim youth and examine their relationship with prosociality, and attitudes towards death. The second objective was to develop an instrument to measure Afterlife Hope Expectations (AHE) and Afterlife Fear Expectations (AFE) and examine whether there is a balance between AHE and AFE among Muslim youth. The third objective was to develop an instrument to measure Compulsory Temporary Afterlife Punishment Beliefs (CTAPB) and determine the extent of this phenomenon among Muslim youth. The fourth objective was to develop an instrument to measure Temporary Afterlife Punishment Expectations (TAPE) and examine their relationship with prosociality. After validating the content of the scales, data were collected from two groups of Muslim youth from two Muslim countries (Jordan, N = 605 and Malaysia, N = 303). Most of the Jordanian participants were recruited from twelve faculties in four universities that were chosen randomly. Malaysian participants were purposively selected from diverse academic backgrounds from Universiti Putra Malaysia. Exploratory and confirmatory factor analyses supported the validity of the Arabic and Malaysian versions of the five scales. The models showed very good fit to the Jordanian the Malaysian data. Following the validation of the Afterlife Reward and Punishment Beliefs and Expectations ARPB&E scales, four hypotheses were examined. Drawing on the theoretical traditions of meaning management theory, the eudemonistic tradition, self-control theory, and a modified version of the Protestant Ethic hypothesis, the study predicted that: 1) Afterlife Reward and Punishment Beliefs ARPB would be positively associated with integrity, death anxiety, and death acceptance; 2) Muslim youth would display high levels of Afterlife Hope Expectation AHE and low levels of Afterlife Fear Expectation AFE; 3) Compulsory Temporary Afterlife Punishment Beliefs CTAPB would be prevalent among Muslim youth; and 4) Temporary Afterlife Punishment Expectations TAPE would be negatively associated with integrity and self-control, and positively associated with rule breaking ability. As hypothesized, the results indicated that Afterlife Reward and Punishment Beliefs ARPB was positively associated with integrity, death anxiety, and death acceptance. The results showed a high level of Afterlife Hope Expectation AHE and a low level of Afterlife Fear Expectation AFE among both Jordanian and Malaysian youth. Results further indicated that the doctrine of Compulsory Temporary Afterlife Punishment Beliefs CTAPB is prevalent despite its contradiction with the Balance doctrine as defined by Islamic theology. Path analysis results showed a negative association between Temporary Afterlife Punishment Expectations TAPE on prosociality (integrity, rule breaking ability, and self-control) among Jordanian and Malaysian youth. In general, the results indicate a positive relationship between Afterlife Reward and Punishment Beliefs ARPB and the psychological state of Muslim youth. However, the imbalance between Afterlife Hope Expectation AHE and Afterlife Fear Expectation AFE, the prevalence of Compulsory Temporary Afterlife Punishment Beliefs CTAPB, and the negative effects of Temporary Afterlife Punishment Expectations TAPE on selfcontrol, rule breaking ability, and integrity provide partial explanation as to why Afterlife Reward and Punishment Beliefs and Expectations ARPB&E may not efficiently motivate prosociality among Muslim youth. The findings call for religious institutions to review and reconsider their methods of teaching Afterlife Reward and Punishment Beliefs and Expectations ARPB&E. The study findings confirm the need for further investigation into Muslim youth afterlife beliefs.